2013
DOI: 10.1371/journal.pone.0081265
|View full text |Cite
|
Sign up to set email alerts
|

Aphotic N2 Fixation in the Eastern Tropical South Pacific Ocean

Abstract: We examined rates of N2 fixation from the surface to 2000 m depth in the Eastern Tropical South Pacific (ETSP) during El Niño (2010) and La Niña (2011). Replicated vertical profiles performed under oxygen-free conditions show that N2 fixation takes place both in euphotic and aphotic waters, with rates reaching 155 to 509 µmol N m−2 d−1 in 2010 and 24±14 to 118±87 µmol N m−2 d−1 in 2011. In the aphotic layers, volumetric N2 fixation rates were relatively low (<1.00 nmol N L−1 d−1), but when integrated over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
137
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 107 publications
(155 citation statements)
references
References 71 publications
18
137
0
Order By: Relevance
“…Taken together, our data suggest that by using Advantec filters, detection of low BNF rates is more likely. This finding is important because BNF rates in mesopelagic waters and other "unusual" habitats are often equal to or even lower than our rates (Fernandez et al, 2011;Bonnet et al, 2013;Dekaezemacker et al, 2013;Rahav et al, 2013;Benavides et al, 2015;Löscher et al, 2016). Consequently, it would be desirable to test whether rates determined for these environments (and the biogeochemical significance derived from such rates) are underestimates due to the use of 0.7 µm pore size GF/F filters.…”
Section: The Effect Of Different Retention By Gf/f and Advantec Filtementioning
confidence: 75%
See 1 more Smart Citation
“…Taken together, our data suggest that by using Advantec filters, detection of low BNF rates is more likely. This finding is important because BNF rates in mesopelagic waters and other "unusual" habitats are often equal to or even lower than our rates (Fernandez et al, 2011;Bonnet et al, 2013;Dekaezemacker et al, 2013;Rahav et al, 2013;Benavides et al, 2015;Löscher et al, 2016). Consequently, it would be desirable to test whether rates determined for these environments (and the biogeochemical significance derived from such rates) are underestimates due to the use of 0.7 µm pore size GF/F filters.…”
Section: The Effect Of Different Retention By Gf/f and Advantec Filtementioning
confidence: 75%
“…However, nitrogenase (nifH) gene sequencing has uncovered an almost ubiquitous distribution of diverse and presumably heterotrophic diazotrophs (Zehr et al, 1998;Farnelid et al, 2011). Notably, these organisms are even found in high-latitude, deep, cold, or coastal waters where cyanobacteria are few or absent (e.g., Fernandez et al, 2011;Blais et al, 2012;Bonnet et al, 2013) and their lifestyles and how they impact biogeochemical element cycling seems fundamentally different from photoautotrophic diazotrophs (Rahav et al, 2013;Farnelid et al, 2014;Moisander et al, 2014;Benavides et al, 2015;Bentzon-Tilia et al, 2015a). This has inspired many investigators to hypothesize that global N inputs by BNF could potentially be much higher than previously thought.…”
Section: Introductionmentioning
confidence: 99%
“…However, it must be borne in mind that different diazotroph phylotypes have different responses to daily fluctuations in irradiance (e.g., Church et al, 2005). Finally, the presence and activity of heterotrophic diazotrophs in aphotic waters (e.g., Hewson et al, 2007;Bonnet et al, 2013;Rahav et al, 2013) challenges this strict control and defines physiological differences among diazotrophic species.…”
Section: Impact Of Physical Factors On Diazotrophymentioning
confidence: 99%
“…Recent culture and field studies indicate that diazotrophy can continue upon exposure to dissolved inorganic nitrogen (nitrate and ammonium) as long as phosphate is available (reviewed in Knapp, 2012). Furthermore, active N 2 fixation in dissolved inorganic nitrogen-rich environments suggests that restricting diazotrophy studies to the upper ocean layer of the tropics and subtropics can result in large underestimations of N 2 fixation rates (Raimbault and Garcia, 2008;Benavides et al, 2011;Sohm et al, 2011b;Bonnet et al, 2013). Foster et al (2009) found UCYN-A over the Equatorial upwelling region in the Gulf of Guinea.…”
Section: Nutrient and Trace Metal Controlsmentioning
confidence: 99%
See 1 more Smart Citation